Maslahah Mursalah Implementasinya Pada Transaksi Ekonomi - Ajuna, Luqmanul Hakiem (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Economic transactions in the financial services sector are increasing in latest years, this is indicated by the growing development of Islamic financial institutions in Indonesia supported by government policies regarding the sector. Later worries emerged as the financial sector was rapidly advancing, namely increasingly fierce competition between the managerial financial sectors in question which had an impact on the neglect of sharia values in the service products it sparked. There are many methods of ijtihad, beside Quranic and Sunnah method, that can be used as an alternative choice in maintaining sharia values in sharia financial sector products. For example the method of ijtihad maslahah mursalah which, although it is currently still debated among Muslim scholars and scholars, has an influence on the Islamic financial sector.